Screening of genes interacting with high myopia and neuropsychiatric disorders - Yang Liu; Yang Liu; Wen Zhang; Zhong-Qi Xue; Fang-Xia Zhang; Wei-Gang Xu; Wen-Juan Zhuang (Scientific Reports, 2023)
Abstract Clinical studies have demonstrated an association between high myopia (HM) and neuropsychiatric disorders; however, the underlying mechanism of the association is not clear. We used whole exome sequencing (WES) in combination with the Genetic Variants Classification Criteria and Guidelines published by the American College of Medical Genetics (ACMG) and bioinformatics analysis to clarify the interrelationship between candidate genes. Causative genes for ocular diseases (45.38%) followed by neuropsychiatric disorders (22.69%) accounted for the highest proportion of genes that exhibited high pathogenicity in HM patients were found. Four pathogenic gene mutations were identified according to ACMG guidelines: c.164_165insACAGCA and c.C1760T in POLG, c.G1291A in COL5A1, and c.G10242T in ZNF469. Three causative genes for neuropsychiatric diseases, PTPRN2, PCDH15 and CDH23, were found to fall at the HM locus. The above results suggest that these genes may interact in high myopia and neuropsychiatric diseases.